2017
DOI: 10.1007/s41230-017-7098-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ti(C,N) precipitates on austenite growth of micro-alloyed steel during continuous casting

Abstract: A ccording to thermal mechanical control process and relaxation-precipitation controlling phase transformation technique during hot rolling process, the microstructure of steel can be refined by the addition of Ti-Nb microalloys [1,2] . A significant improvement in strength, toughness and weldability of steel can be obtained by Ti(C,N) precipitation. However, the hot ductility of micro-alloyed steels remains very poor during continuous casting, which leads to the formation of transverse cracks during the strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Combined with the second phase precipitation model [28,29], for the Nb, C, and N components of the test steel, the precipitation-time-temperature curves of Nb(C,N) in austenite are calculated and presented in Figure 16, In the typical "C shape" curves, t 0.05 and t 0.95 are the start and finish times of precipitation, respectively. It is shown that the nose temperature for boundary nucleation is 980 • C, and for homogeneous nucleation it is 850 • C. Comparing the influence of three kinds of thermal schedules on ductility of HG785 steel slab in III brittleness area, presented in Figure 17 [30], thin ferrite film will be formed in the brittle trough area 800 °C under the pattern 1 and pattern 2 thermal schedules. Intergranular failure can occur during the austenite to ferrite transformation when a thin ferrite film has been formed around the austenite grains [31].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Combined with the second phase precipitation model [28,29], for the Nb, C, and N components of the test steel, the precipitation-time-temperature curves of Nb(C,N) in austenite are calculated and presented in Figure 16, In the typical "C shape" curves, t 0.05 and t 0.95 are the start and finish times of precipitation, respectively. It is shown that the nose temperature for boundary nucleation is 980 • C, and for homogeneous nucleation it is 850 • C. Comparing the influence of three kinds of thermal schedules on ductility of HG785 steel slab in III brittleness area, presented in Figure 17 [30], thin ferrite film will be formed in the brittle trough area 800 °C under the pattern 1 and pattern 2 thermal schedules. Intergranular failure can occur during the austenite to ferrite transformation when a thin ferrite film has been formed around the austenite grains [31].…”
Section: Discussionmentioning
confidence: 97%
“…Those precipitates reduce the bonding force of the grain boundary and hinder the slipping of the grain boundary, and the temperature fluctuation will promote the precipitation of (Ti,Nb)(C,N), which can seriously reduce the ductility of steel [14,32]. Comparing the influence of three kinds of thermal schedules on ductility of HG785 steel slab in III brittleness area, presented in Figure 17 [30], thin ferrite film will be formed in the brittle trough area 800 • C under the pattern 1 and pattern 2 thermal schedules. Intergranular failure can occur during the austenite to ferrite transformation when a thin ferrite film has been formed around the austenite grains [31].…”
Section: Discussionmentioning
confidence: 99%
“…where w C represents the mass fraction of C, A C represents the relative atomic mass of C and [C] represents the solid solution amount of C. The nucleation of solid precipitates occurs first at the grain boundary and then at dislocation, and the uniform nucleation has not happened [35,36]. When the new phase nucleates at grain boundaries, the critical nucleation size, and the critical nucleation work can be calculated by Equations ( 13)-( 15).…”
Section: Dynamics Calculation Of Fine Tin Particlesmentioning
confidence: 99%
“…Owing to the increasingly stringent quality requirements, many studies have investigated the equipment, process, and theoretical principles of continuous casting, particularly for the tundish, which is the final metallurgical element reactor [1][2][3][4][5][6]. To improve the removal of inclusions by the tundish, many flow control devices, such as the turbulence inhibitor, weir-dam, baffle with holes, and filter and gas-curtain device, have been developed to optimize the flow field, increase the residence time, and promote inclusions' removal [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%